Development of a Generic Implementation Strategy of Digital Twins in Logistics Systems under Consideration of the German Rail Transport - Sabina Jeschke (MDPI AG, 2021)
In the course of digitalization, the concept of the digital twin (DT) has become increasingly important in recent years. Hereby, initial concept approaches focus on use cases in industrial production. Although the concept has diverse potential for the asset intensive and increasingly important German rail transport sector. Due to the still low level of research of the DT, there are few empirical values on how this promising concept can be implemented in a target-oriented manner. In a qualitative-explorative research design, this work focuses on answering the question of how a generic implementation strategy (GIS) of DTs in logistics systems of German rail transport can be designed. The central result of this work is a validated GIS which has a sufficient level of detail for the targeted implementation of DTs. Due to its socio-technical system focus, this process model enables user-oriented development and consideration of the complex framework conditions of German rail transport for the first time. The perspective use of the GIS as well as the utilization of the derived recommendations for action contribute to realizing DTs. Consequently, this work is to be regarded as an important instrument for achieving the operational optimization and intelligent management of rail transport assets.